Knowledge Management In Health Care Organizations - Stefanelli, M. (Yearbook of Medical Informatics, 2004)
This review article analyzes theories, methods, and technologies that can be effective in building a socio-technical environment within a health care organization that is able to facilitate the collaboration between individuals in the management of patient care and in expanding scientific and professional knowledge. The article is organized as follows. In section 2, I discuss the nature of knowledge in general and with a particular attention to medical knowledge. The future of health information systems (HIS) is discussed in section 3, which provides also an overview of theories for designing and developing such systems. Section 4 describes different types of collaboration, and reviews the methods and information and communication technologies (ICT), which can be exploited for knowledge creation and interaction management. The potential of workflow management technology for building innovative components within HIS is analyzed in section 5. Finally, section 6 presents the conclusions.